2021
DOI: 10.1016/j.ekir.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Versus Venous Port Site Administration of Nadroparin for Preventing Thrombosis of Extracorporeal Blood Circuits in Patients Receiving Hemodiafiltration Treatment

Abstract: Introduction Administration of low-molecular-weight heparins (LMWHs) is necessary for preventing extracorporeal circuit thrombosis during hemodialysis. A substantial amount of LMWH is removed with online hemodiafiltration (OL-HDF) when administered through the inlet site of the extracorporeal circuit. Consequently, administration of LMWH at the outlet site appears to be more efficient. In this study we aimed to compare the effects of nadroparin calcium (NAD) administered through the outlet versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Thus, we hypothesized that the efficacy of LMWH administered into the arterial blood line for preventing extracorporeal circuit clotting may be potentially reinforced by the additional local anticoagulant effect of citric acid‐based dialysate 23,24 . In line with our study, a significant improvement in visual clotting scores for dialyzers and tubing lines in OL‐HDF, after the switch of single dose LMWH bolus from the arterial blood line to the venous blood line route, has been recently reported 25 . These results indicate loss of LMWH when administered into the arterial blood line route, allowing for a significant LMWH dose reduction with the venous blood line route of injection.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Thus, we hypothesized that the efficacy of LMWH administered into the arterial blood line for preventing extracorporeal circuit clotting may be potentially reinforced by the additional local anticoagulant effect of citric acid‐based dialysate 23,24 . In line with our study, a significant improvement in visual clotting scores for dialyzers and tubing lines in OL‐HDF, after the switch of single dose LMWH bolus from the arterial blood line to the venous blood line route, has been recently reported 25 . These results indicate loss of LMWH when administered into the arterial blood line route, allowing for a significant LMWH dose reduction with the venous blood line route of injection.…”
Section: Discussionsupporting
confidence: 76%
“…23,24 In line with our study, a significant improvement in visual clotting scores for dialyzers and tubing lines in OL-HDF, after the switch of single dose LMWH bolus from the arterial blood line to the venous blood line route, has been recently reported. 25 These results indicate loss of LMWH when administered into the arterial blood line route, allowing for a significant LMWH dose reduction with the venous blood line route of injection.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When a fractionated heparin (low molecular weight heparin) is used as a single bolus dose at initiation, injection of the compound should be performed either directly into the venous needle or in the venous blood line, or delayed if injected into the arterial blood line, for preserving an optimal antithrombotic efficiency. It has been clearly shown that immediate injection of the LMWH into the arterial blood line is associated with 20 to 30% loss of the active compound, reduced antithrombotic capacity or higher dosing required to maintain the same efficacy 27,28 …”
Section: Hdf Prescription: Factors To Be Consideredmentioning
confidence: 99%
“…It has been clearly shown that immediate injection of the LMWH into the arterial blood line is associated with 20 to 30% loss of the active compound, reduced antithrombotic capacity or higher dosing required to maintain the same efficacy. 27,28 3.1.4 | HDF prescription modality HDF substitution mode (post-, pre-, or mixed-dilution) relies on few principles: First, post-dilution mode is by default the first line option. It provides the highest efficacy per liter of substituted volume, cost-effectiveness considering reduced water, and electrolytic consumption.…”
Section: Extracorporeal Anticoagulation Managementmentioning
confidence: 99%